Protected cultivation technology for prosperity - Kumar, Raj; Lata, K.; Jadav, J K; Khadda, B S; Rai, A K; Khajuria, S (Indian Horticulture, 2019)
The protected cultivation is important technology for getting higher income, if the implementation of technology carried out precisely with accuracy during preparation of structure, selection of crop and variety, plant-protection measures, marketing of produce etc. The protected cultivation of horticultural crops (short-duration and high-volume) has became the main sources of generating income by farmers. Nowadays, farmers are coming forwards to adopt protected cultivation for better utilization of land and generating of income in Panchmahals district in Gujarat.